Evidence-Based Herbal and Nutritional Treatments for Anxiety in Psychiatric Disorders - Camfield, David; McIntyre, Erica; Sarris, Jerome (Springer International Publishing : Imprint: Springer, 2017)
This book presents the current clinical evidence on the efficacy of herbal and nutritional treatments for anxiety that is experienced in association with psychiatric disorders, and explains how health professionals can apply this knowledge to the benefit of patients presenting with a wide range of symptoms, including comorbid mood disorders. All chapters are written by world-leading researchers who draw on the findings of human clinical trials to provide uncompromising assessments of individual treatments, including herbal anxiolytics with sedative actions, adaptogens, cognitive anxiolytics, and nutraceuticals. Traditional treatments requiring further study - including the plant-based psychotropic Ayahuasca and other phytotherapies of potential value in the treatment of anxiety - are also reviewed. In the closing chapters, a series of helpful case studies are provided by mental health clinicians in order to illustrate how herbal and nutritional treatments can best be integrated into an overall treatment plan for individuals with a range of comorbid diagnoses. Mental health professionals, researchers, and general readers will find that the book provides an excellent review of current scientific knowledge gained from the study of herbal and nutritional treatments, together with important clinical recommendations for their use in patients experiencing clinically significant levels of anxiety.